Exploring models and issuance of Indonesian sovereign Sukūk as a financial instrument for state budget deficit - Rio Erismen Armen; Engku Rabiah Adawiah Engku Ali; Muhamad Abduh; Ahmad Mifdlol Muthohar (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study explores the concept and practice of sovereign sukūk issuances managed by the Government of Indonesia as an instrument to finance the state budget deficit in Indonesia. The government has been forced to employ a budget deficit policy to fund the vast country’s spending. To finance the deficit, the government uses sovereign sukūk (named Sukūk Negara) as one of the financial instruments in addition to sovereign bonds (called Surat Utang Negara). The study uses a qualitative method with library study and interviews as the data collection techniques. The finding shows that the government has developed four models of sovereign sukuk structure, named Ijārah Sale and Leased Back, Ijārah al-Khadamat, Ijārah Asset to be Leased, and Wakālah; with the crux of the four models is Ijārah Sukūk which combines two central Islamic contracts, i.e. sale and purchase contract (al-Bayʿ) and lease contract (al-Ijārah). The sale and purchase of state-owned assets in Indonesian sovereign sukūk issuance is limited to the beneficial right of the asset only (excluding the legal title of the asset). Likewise, the study positively contributes to the two fields, i.e., academic research and the finance industry (particularly Islamic finance involving government and private investors).